Resin composition and prepreg, laminated board and metal foil-clad laminated board containing same
By designing a combination of a specific maleimide-based modifier and benzocyclobutene resin, the problem that substrate materials in the prior art are difficult to meet multiple performance requirements at the same time, and high glass transition temperature and low thermal expansion are achieved The coefficient and excellent dielectric properties meet the needs of high-speed packaging substrate materials.
Patent Information
- Application Number
- CN202311046299.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to meet the multiple performance requirements for substrate materials in high-frequency signal processing at the same time, including low dielectric constant, low dielectric loss tangent, low thermal expansion coefficient, excellent heat resistance and high reliability.
A resin composition is formed by designing a specific maleimide group modified product (component A) and a benzocyclobutene resin (component B) of a specific structure and combining it with each other. The composition contains 20-90 parts of component A and 5-60 parts of component B in the resin composition, which solves the problem of insufficient compatibility between maleimide compounds and low-polar resins and reduces the layer The warpage of the press plate and the metal foil laminate improves the glass transition temperature and heat resistance of the material.
The resin composition, the laminate and metal foil laminate containing the same have the effects of high glass transition temperature, low thermal expansion coefficient, low dielectric constant and low dielectric loss tangent, fully meeting the performance of high-speed packaging substrate materials. Require.
Smart Images

Figure CN119490747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of printed circuit boards, and in particular relates to a resin composition and a prepreg, a laminate and a metal foil-clad laminate containing the same. Background Art
[0002] In recent years, communication technology has entered an era of high-speed signals and high-frequency transmission. The demand for data processing and transmission in communication technology has continued to increase, which has put forward higher requirements on the dielectric properties of related electronic materials to minimize the loss and delay of high-frequency signals. With the advent of the 5G era, represented by high-frequency RF (such as PA, WiGig, WiHD / 60GHz, etc.), large-size chips, DDR5 (3.2-6.4Gbps) and other applications, many performance requirements are put forward for substrate materials, that is, they need to have: low planar thermal expansion coefficient, low dielectric loss tangent, low dielectric constant, higher reliability and higher heat resistance, etc.
[0003] In order to meet the performance requirements of high frequency and high speed of electronic materials, the industry has conducted research on resins with good dielectric properties, including thermosetting polyphenylene ether resins, bismaleimide resins, hydrocarbon resins, etc. At present, composite resin materials containing terminal olefin thermosetting polyphenylene ether resins and triallyl isocyanurate (TAIC) have been used in the mass production of printed circuit boards (PCBs). This substrate has good performance in mechanical properties and heat resistance, but its dielectric constant and dielectric loss tangent are still high, which makes it difficult to meet the requirements of the new generation of communication technology.
[0004] Bismaleimide resin has high monomer activity, and its cured product has high glass transition temperature and good heat resistance, and the finished product has stable performance and can maintain high physical and mechanical properties in a wide temperature range. For example, CN109825081A discloses a thermosetting resin composition, including the following components: a combination of bismaleimide resin and benzoxazine resin or a prepolymer of bismaleimide resin and benzoxazine resin, epoxy resin and active ester; the metal foil laminate prepared by the resin composition has a high glass transition temperature, a low thermal expansion coefficient, a high high temperature modulus and good heat resistance; however, the bismaleimide resin cured product is brittle, has a short storage period, a low dielectric loss tangent, and there is still a lot of room for improvement in dielectric properties.
[0005] Hydrocarbon resin has good performance in toughness and dielectric properties, and is usually used in combination with other thermosetting resins to reduce the dielectric loss tangent and dielectric constant of the material. For example, CN114437435A discloses a hydrocarbon resin-based prepreg, including a reinforcing cloth core and a hydrocarbon resin layer outside thereof, wherein the material of the hydrocarbon resin layer includes: 20-40 parts of hydrocarbon resin, 10-20 parts of bismaleimide resin, 5-10 parts of benzoxazine, 5-10 parts of thermal conductive filler, and 1-5 parts of curing agent; the high-frequency copper-clad laminate prepared using the hydrocarbon resin-based prepreg has good dielectric properties, but the heat resistance of hydrocarbon resin materials is generally insufficient, and the thermal expansion coefficient is large, which makes it difficult to meet the performance requirements of high-speed packaging substrates.
[0006] Therefore, developing a prepreg, laminate, or metal foil-clad laminate with excellent dielectric properties, low thermal expansion coefficient, and high heat resistance, and with lower warping during use to meet packaging reliability requirements is a research focus in this field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a resin composition and a prepreg, a laminate and a metal foil-clad laminate comprising the same. By designing and compounding a specific maleimide-based modifier of component A and a benzocyclobutene resin of a specific structure of component B, the problem of phase separation due to insufficient compatibility between maleimide compounds and low-polarity resins is solved, and the warpage size of the laminate and the metal foil-clad laminate at room temperature and after reflow soldering is further reduced. The resin composition and the laminate and the metal foil-clad laminate comprising the same have excellent properties such as high glass transition temperature and low thermal expansion coefficient, and can fully meet the performance requirements of high-speed packaging substrate materials.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a resin composition, wherein the resin composition comprises the following components in parts by mass:
[0010] Component A 20-90 parts
[0011] Component B 5-60 parts.
[0012] The component A includes an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule.
[0013] The component B is a benzocyclobutene resin, and the benzocyclobutene resin comprises at least one first structural unit and at least one second structural unit;
[0014] The first structural unit has a structure as shown in at least one of Formula IA, Formula IB, and Formula IC:
[0015]
[0016] In formula IC, R1 is vinylene or ethylene.
[0017] The second structural unit has a structure as shown in Formula II:
[0018]
[0019] In formula II, R2 is vinyl, ethyl or phenyl.
[0020] The resin composition provided by the present invention comprises a combination of component A and component B in specific weight parts, and the structures and properties of the two components are specifically as follows:
[0021] Component A: a specific maleimide-based modified substance, which includes an addition reaction product of a maleimide compound a1 containing at least 2 (e.g., 2, 3, or 4, etc.) N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 (e.g., 2, 3, 4, or 5, etc.) primary amino groups in one molecule. The component A is a maleimide mixture, which includes maleimide addition reaction monomers, maleimide addition reaction oligomers or polymers, and also includes maleimide monomers, maleimide oligomers or polymers that do not participate in the addition reaction. The component A contains primary amino groups, secondary amino groups, and carbon-carbon double bonds, and has high reactivity. After curing, the component A has high heat resistance and low planar thermal expansion coefficient.
[0022] Component B: a benzocyclobutene resin of a specific structure, wherein the side chain of the first structural unit contains a benzocyclobutyl structure, and the second structural unit is any one of a polybutadiene structure, a hydrogenated polybutadiene structure, and a polystyrene structure, or a combination of at least two of them. The benzocyclobutene resin is a fully hydrocarbon structure, having a low dielectric constant and a low dielectric loss tangent; at the same time, the molecular structure of the benzocyclobutene resin contains easily reactive alkenyl groups (alkenyl groups from the polybutadiene structure, and benzocyclobutene rings formed by thermal ring opening to form C=C), which can obtain better dielectric properties through thermal curing; and the resin structure contains multiple benzocyclobutene functional groups, which can self-crosslink to obtain a high crosslinking density, improve the defects of hydrocarbon resins based on butadiene, such as low glass transition temperature, high thermal expansion coefficient, and insufficient rigidity, and is very suitable for packaging substrate materials that require thermal expansion coefficient and rigidity.
[0023] The present invention improves the compatibility problem of the resin composition by designing and compounding the components A and B. The resin composition in the varnish state is homogeneous and does not delaminate or precipitate after standing. The prepreg, laminate, and metal foil-clad laminate do not have phase separation or resin aggregation, and have good process performance. At the same time, the components A and B contain more reaction sites and higher reaction activity. The components A and B can each self-polymerize at a suitable temperature, thereby greatly improving the crosslinking density of the resin composition. The cured product has a high glass transition temperature, a low thermal expansion coefficient, and excellent heat resistance, etc., and improves the performance degradation problem of hydrocarbon resins mainly based on butadiene due to insufficient crosslinking density (such as the problem of increased warpage due to a large thermal expansion coefficient and insufficient rigidity). The resin composition and the metal foil-clad laminate containing the resin have a low dielectric constant Dk and a low dielectric loss tangent Df, excellent dielectric properties, and fully meet the performance requirements of high-speed packaging substrate materials.
[0024] In the resin composition provided by the present invention, the mass parts of the component A are 20-90 parts, for example, it can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, preferably 30-90 parts, and more preferably 40-70 parts.
[0025] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0026] The mass proportion of component B is 5-60 parts, for example, it can be 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, preferably 5-40 parts.
[0027] In the resin composition provided by the present invention, component A and component B are compounded with each other in a specific number of parts, so that the resin composition, prepreg, laminate and metal foil-clad laminate have high glass transition temperature, low planar thermal expansion coefficient and excellent heat resistance, and the cured product has excellent warping performance.
[0028] In the resin composition provided by the present invention, if the dosage of component A is too low, the glass transition temperature of the resin composition is low, the thermal expansion coefficient increases, the heat resistance decreases, and the deformation resistance, especially the deformation resistance at high temperature, deteriorates, resulting in serious warping and affecting the packaging reliability; if the dosage of component A is too high, the dielectric loss of the resin composition is high and the dielectric performance is reduced; if the dosage of component B is too low, the dielectric loss of the resin composition is large; if the dosage of component B is too high, the heat resistance of the resin composition decreases, the thermal expansion coefficient increases, and the deformation resistance deteriorates.
[0029] Preferably, the molar percentage of the first structural unit in the benzocyclobutene resin is ≥5%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, and specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific points included in the range, and it is further preferably ≥30%, and further preferably 30-60%.
[0030] Preferably, the molar percentage of the second structural unit in the benzocyclobutene resin is 15-90%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] As a preferred technical solution of the present invention, in the benzocyclobutene resin, the molar percentage of the first structural unit containing a benzocyclobutene group in the side chain is 5-80%, more preferably 30-60%, and the molar percentage of the second structural unit is 15-90%, more preferably 30-70%, thereby making the benzocyclobutene resin have both excellent reactivity and dielectric properties, thereby, in combination with other resins, the thermosetting crosslinking reaction activity and crosslinking density can be improved, thereby improving the heat resistance and mechanical properties of the resin composition. If the molar percentage of the first structural unit is too low, the crosslinking density of the benzocyclobutene resin itself will be reduced, thereby affecting the glass transition temperature, thermal expansion coefficient, etc. of the resin composition; if the molar percentage of the first structural unit is too high, on the one hand, the synthesis difficulty and production cost of the benzocyclobutene resin will be increased, and on the other hand, a large amount of unreacted benzocyclobutene groups will remain in the resin composition, and the residual benzocyclobutene groups in the subsequent use of the cured product will further react to generate a large amount of stress, affecting the warping performance of the resin composition, the laminated board and the metal foil-clad laminated board.
[0032] Preferably, the benzocyclobutene resin further comprises a third structural unit, and the third structural unit has a structure as shown in Formula IIIA and / or Formula IIIB:
[0033]
[0034] It should be noted that the benzocyclobutene resin is a polymer segment structure, including at least one (preferably multiple) first structural units, at least one (preferably multiple) second structural units and optionally a third structural unit; the present invention does not limit the connection sequence of the above structural units, and any connection sequence / connection method feasible in chemistry is within the scope of the present invention.
[0035] Preferably, the molar percentage of the third structural unit in the benzocyclobutene resin is ≤40%, for example, it can be 0, 1%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35% or 40% and specific values between the above values. Due to space limitations and for simplicity, the present invention no longer exhaustively lists the specific values included in the range, and is further preferably ≤30%, further preferably ≤20%, and most preferably ≤10%. Thus, the curing degree of the benzocyclobutene resin and the resin composition containing the same is increased, and has a higher glass transition temperature, a lower thermal expansion coefficient, etc.
[0036] It should be noted that the benzocyclobutene resin of the present invention can be divided into two categories according to the type of the first structural unit: type A benzocyclobutene resin and type B benzocyclobutene resin; the component B (benzocyclobutene resin) includes type A benzocyclobutene resin and / or type B benzocyclobutene resin. The first structural unit of the type A benzocyclobutene resin has a structure as shown in Formula IA and / or Formula IB, and the first structural unit of the type B benzocyclobutene resin has a structure as shown in Formula IC.
[0037] Preferably, the mass percentage of the first structural unit (the structure represented by Formula IA and / or Formula IB) in the Class A benzocyclobutene resin is ≥10%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, preferably ≥30%, and more preferably 30-80%.
[0038] Exemplarily, the preparation method of the type A benzocyclobutene resin comprises: a butadiene-based polymer and a benzocyclobutene monomer The reaction is carried out to obtain the type A benzocyclobutene resin; the butadiene-based polymer is polybutadiene or butadiene-styrene copolymer, which contains a structural unit of butadiene 1,2-polymerization
[0039] Preferably, the reaction is carried out in the presence of an organic peroxide.
[0040] Preferably, the organic peroxide includes any one of tert-butyl isopropylphenyl peroxide, dicumyl peroxide, benzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, and 1,1-di(tert-butylperoxy)-3,3,5-dimethylcyclohexane, or a combination of at least two thereof.
[0041] Preferably, the reaction temperature is 80-130°C, for example, it can be 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or 125°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0042] Preferably, the reaction time is 4-16 h, for example, it can be 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Based on the preparation method of the type A benzocyclobutene resin, the structural unit of butadiene 1,2-polymerization in the butadiene-based polymer It may be self-polymerized in the presence of an organic peroxide, so that the type A benzocyclobutene resin further comprises a fourth structural unit, wherein the fourth structural unit is a polybutadiene structural unit. A structural unit with a ring structure formed by polymerization.
[0044] Exemplarily, the preparation method of the B-type benzocyclobutene resin comprises: reacting a butadiene-based polymer with a 4-halogenated benzocyclobutene The B-type benzocyclobutene resin is obtained by coupling reaction; the butadiene-based polymer is polybutadiene or butadiene-styrene copolymer, which contains 1,2 polymerized structural units Hal is a halogen, for example, Cl, Br or I.
[0045] Preferably, the coupling reaction is carried out in the presence of a palladium catalytic system.
[0046] Preferably, the palladium catalytic system comprises a palladium catalyst and an organic phosphine ligand.
[0047] Preferably, the palladium catalyst is palladium acetate, and the organic phosphine ligand is tri(o-methylphenyl)phosphine.
[0048] Preferably, the coupling reaction is carried out in the presence of an acid binding agent.
[0049] Preferably, the acid binding agent comprises an organic base, more preferably triethylamine.
[0050] Preferably, the coupling reaction is carried out in an inert protective atmosphere, which includes any one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.
[0051] Preferably, the temperature of the coupling reaction is 60-100°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, as well as specific values between the above-mentioned points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0052] Preferably, the coupling reaction time is 5-36 h, for example, it can be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 24 h, 28 h, 32 h or 34 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0053] Preferably, the preparation of the type A benzocyclobutene resin and the type B benzocyclobutene resin each independently further includes an optional hydrogenation step, the hydrogenation reaction can be carried out before and / or after the aforementioned reaction, and the hydrogenation reaction can be complete hydrogenation (i.e., all C=C on the main chain and side chain of the type A benzocyclobutene resin and the type B benzocyclobutene resin are hydrogenated, preferably after the reaction) or partial hydrogenation (can be carried out before or after the reaction). The hydrogenation reaction hydrogenates all or part of the C=C double bonds from the butadiene-based polymer (polybutadiene and / or styrene-butadiene copolymer) to form a saturated carbon chain; thereby, it helps to further optimize the dielectric properties of the benzocyclobutene resin.
[0054] Preferably, the number average molecular weight of the benzocyclobutene resin is 1000-200000, for example, it can be 2000, 5000, 8000, 10000, 12000, 15000, 20000, 50000, 80000, 100000, 120000, 150000 or 180000, as well as specific values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Preferably, the number average molecular weight of the type A benzocyclobutene resin is 1000-200000, for example, it can be 2000, 5000, 8000, 10000, 12000, 15000, 20000, 50000, 80000, 100000, 120000, 150000 or 180000, as well as specific values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Preferably, the number average molecular weight of the type B benzocyclobutene resin is 1000-20000, for example, it can be 2000, 5000, 8000, 10000, 12000, 15000 or 18000, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0057] Preferably, the maleimide compound a1 contains two N-substituted maleimide groups in one molecule.
[0058] Preferably, the maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenoxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenyl)cyclohexane oxy)phenyl)methane, 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4' - any one or a combination of at least two of bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether, bis(4-(4-maleimidophenoxy)phenyl)ether, and further preferably any one or a combination of at least two of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane, and 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane.
[0059] Preferably, the amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl any one of or a combination of at least two of the following: 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, and 4,4'-diamino-3,3'-dihydroxybiphenyl; further The step is preferably any one or a combination of at least two of a siloxane compound containing at least two primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, and 2,2-bis(4-(4-aminophenoxy)phenyl)propane.
[0060] As a preferred technical solution of the present invention, the amine compound a2 includes a siloxane compound containing two primary amino groups, which can obtain a resin composition with a low planar expansion coefficient.
[0061] Exemplarily, the siloxane compound containing two primary amino groups can use commercially available products, including but not limited to: PAM-E (side chain methyl type, functional group equivalent 130 g / mol), KF-8010 (side chain methyl type, functional group equivalent 430 g / mol), X-22-161A (side chain methyl type, functional group equivalent 800 g / mol), X-22-161B (side chain methyl type, functional group equivalent 800 g / mol) of Shin-Etsu Chemical Co., Ltd. Any one of KF-8012 (side chain methyl type, functional group equivalent 1500g / mol), KF-8008 (side chain methyl type, functional group equivalent 5700g / mol), X-22-9409 (side chain phenyl type, functional group equivalent 670g / mol), X-22-1660B-3 (side chain phenyl type, functional group equivalent 2200g / mol) or a combination of at least two thereof.
[0062] Preferably, in component A, the addition reaction of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is carried out in an organic solvent; the type of the organic solvent is not particularly limited, and propylene glycol monomethyl ether is further preferred.
[0063] In the present invention, the temperature of the addition reaction of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited, as long as the maleimide compound a1 and the amine compound a2 react. As a preferred technical scheme of the present invention, from the perspective of reaction rate and solvent boiling point, the temperature of the addition reaction is preferably 100-130°C, for example, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C or 128°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0064] In the present invention, the addition reaction time of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited. Preferably, the addition reaction time is 2-10 h, for example, it can be 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 3-8 h is further preferred.
[0065] Preferably, the resin composition further includes 1-50 parts of component C by mass, for example, component C can be 2 parts, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] The component C comprises any one of epoxy resin, anhydride compound, active ester compound and compound having carbon-carbon unsaturated double bond in molecule or a combination of at least two thereof, preferably compound having carbon-carbon unsaturated double bond in molecule.
[0067] Preferably, the compound having carbon-carbon unsaturated double bonds in the molecule includes any one of unsaturated polyphenylene ether, multifunctional vinyl compound, allyl compound, acrylate compound, acenaphthylene compound, polybutadiene, or a combination of at least two thereof.
[0068] Preferably, the unsaturated polyphenylene ether comprises polyphenylene ether terminated with an unsaturated group; wherein the unsaturated group may be any one of vinylbenzyl, vinylphenyl, acrylate, and methacrylate, or a combination of at least two thereof.
[0069] As a preferred technical solution of the present invention, in the resin composition, from the perspective of achieving a high glass transition temperature and a low planar thermal expansion coefficient of the cured product, based on 100 parts by total mass of component A, component B and optionally component C, component A is 20-90 parts, for example, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, preferably 30-90 parts, and more preferably 40-70 parts.
[0070] As a preferred technical solution of the present invention, in the resin composition, from the perspective of achieving a low dielectric loss factor of the cured product, based on the total mass of component A, component B and optionally component C as 100 parts, the component B is 5-60 parts, for example, it can be 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, preferably 5-40 parts.
[0071] Preferably, the resin composition further comprises 5-30 parts by mass of a thermoplastic polymer, and the thermoplastic polymer may be 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0072] Preferably, the thermoplastic polymer includes any one of styrene polymers, hydrogenated styrene polymers, and polyolefin resins, or a combination of at least two of them.
[0073] Preferably, the styrene polymer is a copolymer comprising an olefin structural unit and a styrene structural unit. The olefin structural unit is derived from an olefin monomer, such as a structural unit derived from butadiene, a structural unit derived from isoprene, etc.; the styrene structural unit is derived from a styrene monomer, such as a structural unit derived from styrene, a structural unit derived from styrene with a substituent, etc. In addition to the olefin structural unit and the styrene structural unit, the styrene polymer may also contain structural units other than the olefin structural unit and the styrene structural unit, such as a structural unit derived from an epoxy group, a structural unit derived from an amino group, a structural unit derived from maleic anhydride, etc.
[0074] The styrenic polymer may be a random copolymer or a block copolymer.
[0075] The hydrogenated styrene-based polymer is obtained by partially or completely hydrogenating the structural units of the styrene-based polymer derived from olefins.
[0076] The styrene-based polymer and hydrogenated styrene-based polymer can be commercially available products, illustratively including but not limited to: Ricon 100 (butadiene-styrene copolymer, Cray Valley), Ricon 181 (butadiene-styrene copolymer, Cray Valley), Tuftec H1051 (hydrogenated styrene-butadiene copolymer, styrene content of 42% by mass, Asahi Kasei Chemicals Corporation), Tuftec M1913 (hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, styrene content of 30% by mass, Asahi Kasei Chemicals Corporation) any one or a combination of at least two thereof.
[0077] Preferably, the resin composition further includes 0.01-5 parts of a curing accelerator by mass, and the curing accelerator may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 4.8 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0078] Preferably, the curing accelerator includes any one of an acidic curing accelerator, an organic phosphorus curing accelerator, an imidazole curing accelerator, a pyridine curing accelerator, an amine curing accelerator, a peroxide, and an organic metal salt, or a combination of at least two thereof.
[0079] Exemplarily, the acidic curing accelerator includes p-toluenesulfonic acid, etc., the organic phosphorus curing accelerator includes triphenylphosphine, etc., the imidazole curing accelerator includes imidazole and / or imidazole derivatives (such as 2-methylimidazole, 2-ethylimidazole or 2-ethyl-4-methylimidazole, etc.), the pyridine curing accelerator includes pyridine and / or pyridine derivatives (such as 4-dimethylaminopyridine), the amine curing accelerator includes secondary amine compounds, tertiary amine compounds or quaternary ammonium salts, the peroxide includes diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis (tert-butyl peroxy) hexyne-3, 2,5-dimethyl-2,5-bis (tert-butyl peroxy) hexane or α, α'-bis (tert-butyl peroxy) diisopropylbenzene, etc., and the organic metal salt includes zinc naphthenate, cobalt naphthenate, tin octoate or cobalt octoate, etc. The curing accelerator can be used alone or in combination of at least two.
[0080] Preferably, the resin composition further includes 5-250 parts of inorganic filler by mass, and the inorganic filler can be 8 parts, 10 parts, 20 parts, 30 parts, 50 parts, 70 parts, 90 parts, 100 parts, 110 parts, 130 parts, 150 parts, 170 parts, 190 parts, 200 parts, 210 parts or 230 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0081] As a preferred technical solution of the present invention, the inorganic filler helps to improve the heat resistance, moisture and heat resistance and mechanical properties of the resin composition and reduce the thermal expansion coefficient. If the amount of inorganic filler is too much, the dielectric loss tangent of the resin composition will increase, which is not conducive to signal transmission.
[0082] The present invention is not particularly limited to the type of inorganic filler, and exemplarily includes but is not limited to: any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, molybdenum oxide, zinc oxide, zinc molybdate, zinc borate, zinc stannate, titanium dioxide, strontium titanate, barium titanate, barium sulfate, clay, kaolin, talc, mica, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber, hollow glass. In order to make the resin composition have higher heat resistance, moisture and heat resistance and dimensional stability, it is preferably any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber, hollow glass. Wherein, the silicon dioxide can be any one or at least two combinations of crystalline silica, fused silica, amorphous silica, spherical silica, hollow silica, and more preferably spherical silica.
[0083] The average particle size of the inorganic filler (D 50 ) is not particularly limited, but from the perspective of dispersibility, the average particle size (D 50 ) is preferably 0.01-20 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or 18 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 0.01-10 μm is further preferred. Inorganic fillers of different types, different particle size distributions or different average particle sizes can be used alone or in combination as needed.
[0084] For example, the particle size of the inorganic filler is measured using a MS3000 Malvern laser particle size analyzer.
[0085] Preferably, the inorganic filler comprises a surface-treated filler, and the surface treatment agent for the surface treatment comprises any one of a silane coupling agent, an organosilicon oligomer, and a titanate coupling agent, or a combination of at least two thereof, and the silane coupling agent is more preferred.
[0086] Preferably, the resin composition further comprises 0.01-10 parts of a coupling agent in parts by mass, and the coupling agent may be 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0087] Preferably, the coupling agent comprises a silane coupling agent.
[0088] The present invention does not particularly limit the type of silane coupling agent, and illustratively includes but is not limited to: any one of epoxy silane coupling agent, amino silane coupling agent, vinyl silane coupling agent, styrene silane coupling agent, isobutylene silane coupling agent, acryl silane coupling agent, urea silane coupling agent, mercapto silane coupling agent, chloropropyl silane coupling agent, sulfide silane coupling agent, isocyanate silane coupling agent or a combination of at least two thereof.
[0089] Preferably, the resin composition further comprises a flame retardant. The flame retardant is not particularly limited, and can be selected from halogen or non-halogen flame retardants that are soluble or insoluble in an organic solvent. Exemplarily, the non-halogen flame retardant includes an inorganic phosphorus flame retardant, an organic phosphorus flame retardant, a metal hydrate, and the like.
[0090] From the perspective of environmental issues and excellent dielectric properties, the flame retardant is preferably an organophosphorus flame retardant. Exemplarily, the organophosphorus flame retardant includes aromatic phosphates, monosubstituted phosphonic acid diesters, disubstituted phosphinates, metal salts of disubstituted phosphinates, organic nitrogen-containing phosphorus compounds, cyclic organophosphorus compounds, and the like.
[0091] For example, the aromatic phosphates include triphenyl phosphate, tricresyl phosphate, tri(xylene) phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylene phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di(2,6-dimethylphenyl) phosphate), 4,4'-biphenyl bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis(diphenyl phosphate), etc.; the monosubstituted phosphonic acid diesters include divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, etc.; the disubstituted phosphinates include Diphenylphosphinate phenyl ester, diphenylphosphinate methyl ester, etc.; the metal salt of the disubstituted phosphinate includes metal salts of dialkylphosphinate, metal salts of diallylphosphinate, metal salts of divinylphosphinate, metal salts of diarylphosphinate, etc.; the organic nitrogen-phosphorus compound includes phosphazene compound, melamine phosphate, melamine polyphosphate, melamine pyrophosphate, etc.; the cyclic organic phosphorus compound includes 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, etc. The flame retardant can be used alone or in combination of at least two.
[0092] A solvent may also be added to the resin composition, and the amount of the solvent added is selected by a person skilled in the art based on experience and process requirements, so that the resin composition reaches a viscosity suitable for use, so as to facilitate coating, impregnation, processing, etc. of the resin composition. In the subsequent drying, semi-curing or full curing stage, the solvent in the resin composition will partially or completely volatilize.
[0093] The solvent of the present invention is not particularly limited, and generally, ketones such as acetone, butanone, and cyclohexanone, aromatic hydrocarbons such as toluene and xylene, esters such as ethyl acetate and butyl acetate, alcohols such as methanol, ethanol, or butanol, alcohols such as ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, carbitol, or butyl carbitol, and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, or N-methyl-2-pyrrolidone can be selected; the solvent can be used alone or in combination of two or more. Ketones such as acetone, butanone, and cyclohexanone, and aromatic hydrocarbons such as toluene and xylene are preferred.
[0094] The resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the resin composition to obtain the resin composition.
[0095] In a second aspect, the present invention provides a resin film, wherein the material of the resin film includes the resin composition as described in the first aspect.
[0096] Preferably, the resin film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
[0097] Preferably, the drying and semi-curing temperatures are each independently 100-180°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0098] In a third aspect, the present invention provides a resin-coated copper foil, wherein the resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in the first aspect.
[0099] Preferably, the resin-coated copper foil is obtained by coating the resin composition on a copper foil and then drying and / or semi-curing the resin composition.
[0100] Preferably, the drying and semi-curing temperatures are each independently 100-180°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0101] In a fourth aspect, the present invention provides a prepreg, comprising a substrate and the resin composition as described in the first aspect attached to the substrate.
[0102] Preferably, the resin composition is attached to the substrate by impregnation and drying.
[0103] Preferably, the raw material of the substrate includes any one or a combination of at least two of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers; for example, glass fiber cloth, organic fiber cloth, glass fiber paper, quartz glass fiber blended cloth, non-woven fabric, quartz cloth, wood pulp paper, etc.
[0104] Preferably, the glass fiber cloth includes any one of Q-glass fiber cloth, E-glass fiber cloth, D-glass fiber cloth, L-glass fiber cloth, M-glass fiber cloth, S-glass fiber cloth, T-glass fiber cloth, and NE-glass fiber cloth, or a combination of at least two thereof.
[0105] Preferably, the organic fiber cloth includes any one of polyimide fiber cloth, polyamide fiber cloth, polyester fiber cloth, polyphenylene ether fiber cloth, and liquid crystal polymer fiber cloth, or a combination of at least two of them.
[0106] Illustratively, the method for preparing the prepreg is: impregnating a substrate with a resin glue of the resin composition, and then drying to obtain the prepreg.
[0107] Preferably, the solvent of the resin glue solution includes any one of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene and xylene, or a combination of at least two of them.
[0108] Preferably, the drying temperature is 100-180°C, for example, it can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0109] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0110] In a fifth aspect, the present invention provides a laminate comprising at least one prepreg as described in the fourth aspect.
[0111] In a sixth aspect, the present invention provides a metal foil-clad laminate, comprising at least one of the resin film as described in the second aspect, the resin-coated copper foil as described in the third aspect, and the prepreg as described in the fourth aspect.
[0112] Preferably, the metal foil in the metal foil-clad laminate includes any one of copper foil, aluminum foil, nickel foil, alloy foil, or a combination of at least two of them, and copper foil is more preferred.
[0113] The metal foil is copper foil, and the metal foil-clad laminate is a copper-clad laminate.
[0114] Preferably, the number of prepregs in the metal foil-clad laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0115] Exemplarily, the method for preparing the metal foil-clad laminate comprises: laminating metal foil on one side or both sides of a prepreg and curing to obtain the metal foil-clad laminate; or, stacking at least two prepregs into a laminate, and then laminating metal foil on one side or both sides of the laminate and curing to obtain the metal foil-clad laminate.
[0116] Preferably, the curing is carried out in a press.
[0117] Preferably, the curing temperature is 170-280°C, for example 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 200-250°C is further preferred.
[0118] Preferably, the curing pressure is 10-60 kg / cm 2 , for example, it can be 15kg / cm 2 , 20kg / cm 2 , 25kg / cm2 、30kg / cm 2 、35kg / cm 2 , 40kg / cm 2 , 45kg / cm 2 , 50kg / cm 2 or 55kg / cm 2 , as well as specific point values between the above point values, due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific point values included in the range.
[0119] Preferably, the curing time is 30-300 min, for example, 40 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 30-180 min is further preferred.
[0120] In a seventh aspect, the present invention provides a printed circuit board, comprising at least one of the resin film as described in the second aspect, the resin-coated copper foil as described in the third aspect, the prepreg as described in the fourth aspect, the laminate as described in the fifth aspect, and the metal foil-clad laminate as described in the sixth aspect.
[0121] Compared with the prior art, the present invention has the following beneficial effects:
[0122] (1) In the resin composition provided by the present invention, component A is a specific maleimide-based modified substance, which has high heat resistance, reactivity and low planar thermal expansion coefficient, and component B is a benzocyclobutene resin of a specific structure, which has low dielectric constant and low dielectric loss tangent, and high reactivity. Through the design and mutual compounding of component A and component B, the problem of phase separation due to insufficient compatibility between maleimide compounds and low-polarity resins is solved, and the warpage size of laminated boards and metal foil-clad laminated boards at room temperature and after reflow is further reduced. The resin composition and the metal foil-clad laminated board containing the resin composition have high glass transition temperature, low thermal expansion coefficient, low dielectric constant and low dielectric loss tangent, etc., which fully meet the performance requirements of high-speed packaging substrate materials.
[0123] (2) The present invention has no compatibility problems such as resin agglomeration and precipitation by designing and optimizing the components of the resin composition. The metal foil-clad laminate prepared by impregnating glass fiber cloth with the resin composition in a varnish state has a dielectric constant Dk≤3.7 at 10 GHz, a dielectric loss tangent Df≤0.004, a thermal expansion coefficient XY-CTE≤10 ppm / °C, a glass transition temperature Tg of 220-260°C, and a Δ warpage of ≤57 μm after reflow soldering and at room temperature. The laminate has excellent dielectric properties, heat resistance, and deformation resistance, and fully meets the performance requirements of high-speed packaging substrate materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0124] Figure 1 The infrared spectrum of the benzocyclobutene resin A-BCBS1 provided in Preparation Example 1;
[0125] Figure 2 The infrared spectrum of the benzocyclobutene resin B-BCB2 provided in Preparation Example 4;
[0126] Figure 3 This is the GPC spectrum of the benzocyclobutene resin B-BCB2 provided in Preparation Example 4. DETAILED DESCRIPTION
[0127] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0128] In a specific embodiment, the benzocyclobutene resin is a type A benzocyclobutene resin, the first structural unit of the type A benzocyclobutene resin has a structure as shown in Formula IA and / or Formula IB, and a butadiene-based polymer and a benzocyclobutene monomer ( BCBS for short) is obtained by reacting in the presence of an organic peroxide.
[0129] In another specific embodiment, the benzocyclobutene resin is a type B benzocyclobutene resin, the first structural unit of the type B benzocyclobutene resin has a structure as shown in formula IC, and a butadiene-based polymer and 4-bromobenzocyclobutene are used. The product is obtained by coupling reaction in the presence of a palladium catalytic system.
[0130] In the above method, the butadiene-based polymer used is specifically as follows:
[0131] B2000, polybutadiene, 1,2-polymerized structural units ( The molar percentage of 88% (hereinafter the same) is from Nippon Soda Co., Ltd.;
[0132] B3000, polybutadiene, 92% molar content of structural units formed by 1,2-polymerization, Nippon Soda Co., Ltd.;
[0133] BI3060, partially hydrogenated polybutadiene, 60% molar content of structural units formed by 1,2-polymerization, Nippon Soda Co., Ltd.;
[0134] Ricon 184, butadiene-styrene copolymer (butadiene-styrene resin), 1,2-polymerized structural units with a molar percentage of 30%, styrene structural units The molar percentage is 22%, from Sartomer Company, USA.
[0135] The preparation method of the benzocyclobutene resin in the present invention is described in detail below by means of preparation examples:
[0136] Preparation Example 1
[0137] A benzocyclobutene resin A-BCBS1, the preparation method of which is as follows:
[0138] 50 g of polybutadiene B3000, 50 g of BCBS, and 80 mL of toluene were weighed in a flask and dissolved into a uniform solution, which was heated to reflux temperature in an argon atmosphere. 0.5 g of tert-butylisopropylphenyl peroxide BIPB was dissolved in 20 mL of toluene, and then added dropwise over 40 min. The reaction was allowed to proceed at the reflux temperature of toluene. The reaction was monitored by TLC (thin layer chromatography) until the BCBS raw material point disappeared, the reaction was stopped, and the solution was cooled to obtain benzocyclobutene resin A-BCBS1, which could be used without separation.
[0139] Preparation Example 2-Preparation Example 3
[0140] A benzocyclobutene resin, which differs from Preparation Example 1 in that the types and amounts of raw materials used are different, as specifically shown in Table 1; the process parameters not shown in Table 1 are the same as those in Preparation Example 1.
[0141] Table 1
[0142]
[0143] In Preparation Examples 1 to 3, the structure of the benzocyclobutene resin was characterized and confirmed using a Fourier transform infrared spectrometer (FTIR, IS10FT-IR, Thermo Fisher Scientific). The infrared spectrum of the benzocyclobutene resin A-BCBS1 provided in Preparation Example 1 is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that 1473cm -1The characteristic absorption at 1495 cm-1 belongs to the four-membered ring of benzocyclobutene, indicating that A-BCBS1 contains benzocyclobutene structure. The TLC column shows that the raw material disappears, indicating that benzocyclobutene is connected to polybutadiene. -1 The absorption of non-aromatic ring structure shows that polybutadiene has double bonds in the ring; but 905cm -1 and 995cm -1 The absorption of the terminal double bond is still very strong, indicating that the polybutadiene structure is partially polymerized.
[0144] As shown in Table 1, the first structural unit (%) represents the mass percentage of the first structural unit (Formula IA and / or Formula IB) containing a benzocyclobutene group in the side chain in the benzocyclobutene resin, which is calculated by the feed amount of BCBS and the mass of the butadiene-based polymer (since thin layer chromatography was used for detection during the preparation process to ensure that the BCBS reaction was complete, the BCBS was completely converted into the first structural unit.
[0145] Preparation Example 4
[0146] A benzocyclobutene resin B-BCB1, the preparation method of which is as follows:
[0147] Add 169.44g 4-bromobenzocyclobutene (4-bromoBCB), 100g polybutadiene B2000, 16.35g tri(o-methylphenyl)phosphine, 7.48g palladium acetate, 500g triethylamine and 1000g acetonitrile to a flask, and stir the reaction at 85°C in an argon atmosphere for 24h. Cool and spin-dry the solvent. Use neutral alumina to quickly pass through the column, spin-dry the solvent to obtain a viscous liquid, add 4 times the amount of toluene to dissolve in toluene, shake well and let stand, and separate the toluene layer. Then spin-dry and concentrate, and vacuum dry to obtain a colorless viscous liquid, i.e., benzocyclobutene resin B-BCB1.
[0148] Preparation Example 5-Preparation Example 6
[0149] A benzocyclobutene resin, which differs from Preparation Example 4 in that the types and amounts of raw materials used are different, as shown in Table 2; the process parameters not shown in Table 2 are the same as those in Preparation Example 4.
[0150] Table 2
[0151]
[0152] In Preparation Examples 4 to 6, the structure of the benzocyclobutene resin was characterized and confirmed using a Fourier transform infrared spectrometer (FTIR, IS10FT-IR, Thermo Fisher). The infrared spectrum of the benzocyclobutene resin B-BCB1 in Preparation Example 4 is shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that 1473cm-1 The characteristic absorption attributable to the four-membered ring of benzocyclobutene indicates that there is a benzocyclobutene structure in the B-BCB1 resin. The TLC column shows that the raw material disappears, indicating that benzocyclobutene is connected to polybutadiene.
[0153] According to the record in GB / T 21863-2008, the molecular weight of benzocyclobutene resin CH-BCB1 was tested by gel permeation chromatography (GPC) based on polystyrene calibration. The obtained GPC spectrum is as follows: Figure 3 As shown, Figure 3 3241 is the viscosity average molecular weight of the benzocyclobutene resin B-BCB1, and its number average molecular weight Mn is 2416.
[0154] In Table 2, the first structural unit (%), the second structural unit (%), and the third structural unit (%) represent the molar percentages of the first structural unit (Formula IC), the second structural unit (Formula II), and the third structural unit (Formula IIIA and / or Formula IIIB) containing a benzocyclobutene group in the side chain in the benzocyclobutene resin; the first structural unit (%) and the second structural unit (%) are calculated by the feed amount of 4-bromoBCB and the molar percentage of the 1,2-polymerized structural unit in the resin raw material (since thin layer chromatography was used for detection during the preparation process to ensure that the 4-bromoBCB reaction was complete). Therefore, 4-bromoBCB is completely converted into the first structural unit, and the difference in the molar percentage of the 1,2-polymerized structural unit and the first structural unit in the resin raw material is the amount of the second structural unit (the corresponding resin raw material is polybutadiene); if the resin raw material is a butadiene-styrene copolymer, the molar percentage of the second structural unit is the difference in the molar percentage of the 1,2-polymerized structural unit and the first structural unit in the resin raw material plus the molar percentage of the styrene structural unit); the third structural unit comes from the resin raw material (polybutadiene or butadiene-styrene copolymer) and is obtained from the raw material manufacturer.
[0155] Preparation Example 7
[0156] The addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, hereinafter referred to as BMI-A1, is prepared as follows:
[0157] Into a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser were added 1 part by weight of an amine compound Kayahard AA (3,3'-diethyl-4,4'-diaminodiphenylmethane, Nippon Kayaku Co., Ltd.), 9 parts by weight of X-22-161A (a siloxane compound containing two primary amino groups at the molecular ends, Shin-Etsu Chemical Co., Ltd.), 30 parts by weight of a maleimide compound BMI-4000 (2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, Yamato Chemical Industry Co., Ltd.), and 30 parts by weight of a solvent propylene glycol monomethyl ether, and the mixture was reacted at 115°C for 360 minutes to obtain BMI-A1.
[0158] Preparation Example 8
[0159] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 9 parts by weight of X-22-161B (a siloxane compound containing two primary amino groups at the molecular ends, Shin-Etsu Chemical Co., Ltd.), 31 parts by weight of the maleimide compound BMI-1000 (bis(4-maleimidophenyl)methane, Yamato Chemical Industry Co., Ltd.), and 30 parts by weight of solvent propylene glycol monomethyl ether were added, and the reaction was kept warm at 115°C for 360 minutes to obtain BMI-A2.
[0160] In the following specific implementation of the present invention, the materials involved are as follows:
[0161] 1. Component A: an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule
[0162] BMI-A1, Preparation Example 7;
[0163] BMI-A2, Preparation Example 8.
[0164] 2. Component B: Benzocyclobutene resin
[0165] Benzocyclobutene resins A-BCBS1 to A-BCBS3 provided in Preparation Examples 1-3;
[0166] Benzocyclobutene resins B-BCB1 to B-BCB3 provided in Preparation Examples 4-6.
[0167] 3. Component B': Benzocyclobutene resin
[0168] CYCLOTENE3022, a benzocyclobutene resin containing siloxane groups in the molecular skeleton, is available from The Dow Chemical Company. The structure is as follows:
[0169]
[0170] 4. Component C
[0171] OPE-2st 1200, polyphenylene ether containing vinyl benzyl groups at the end, Mitsubishi Chemical Corporation.
[0172] 5. Thermoplastic polymers
[0173] Tuftec M1913, hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, Asahi Kasei Chemicals Corporation.
[0174] 6. Inorganic fillers
[0175] SC2500-SXJ, spherical silica modified with aniline siloxane, average particle size D 50 0.5μm, Japan Admatechs Co., Ltd.
[0176] 7. Coupling agent
[0177] KBM-573, phenylaminosilane coupling agent, Shin-Etsu Chemical Co., Ltd.
[0178] Examples 1-10, Comparative Examples 1-5
[0179] A resin composition, the types and amounts of the components are shown in Table 3, Table 4 and Table 5, and the units of the amounts of the components are all "parts".
[0180] A prepreg and a metal foil-clad laminate comprising the resin composition, the preparation method of which is as follows:
[0181] (1) mixing and dispersing the components of the resin composition with toluene solvent in accordance with the formula to form a resin glue solution with a solid content of 65%;
[0182] (2) impregnating glass fiber cloth (3313L glass fiber cloth manufactured by Huber, Taiwan, China) with the resin glue, and then heating and drying in a blast oven at 130° C. for 4 min to convert the resin composition in a varnish state into a resin composition in a semi-cured state, with an average thickness controlled to be 100 μm, to obtain a prepreg;
[0183] (3) Two (or eight) prepregs obtained in step (2) are stacked, and low-profile electrolytic copper foil with a thickness of 12 μm is pressed on the upper and lower sides thereof. The prepregs are heated in a press at 220° C. and 45 kg / cm 2 After curing for 2 hours, a metal-clad laminate with a core board thickness of 0.20 mm (or 0.80 mm) is obtained. After etching the copper foil of the metal-clad laminate, a laminate with a thickness of 0.20 mm (or 0.80 mm) is obtained.
[0184] The metal foil clad laminate / laminated board is subjected to a performance test, and the specific method is as follows:
[0185] (1) Glass transition temperature Tg: A laminate with a length of 60 mm, a width of 10 mm, and a thickness of 0.80 mm was taken as a sample and measured using a dynamic mechanical thermal analyzer (DMA) at a heating rate of 10 °C / min. The result was the transition peak temperature of tanδ in °C.
[0186] (2) Planar thermal expansion coefficient XY-CTE: A laminate with a length of 60 mm, a width of 4 mm, and a thickness of 0.20 mm was taken as a sample, with the glass fiber warp direction in the Y direction and the glass fiber weft direction in the X direction. The sample was dried in an oven at 105°C for 1 hour and then cooled to room temperature in a dryer. The measurement was performed using the thermal mechanical analysis method (TMA), with a heating rate of 10°C / min, from room temperature to 200°C, and two heatings were performed. After the first heating was completed and cooled to room temperature, the sample was re-placed for the second heating. The result was the planar thermal expansion coefficient at the second heating from 60°C to 120°C, and the unit was ppm / °C;
[0187] (3) Dielectric constant Dk and dielectric loss tangent Df: A laminate with a length of 100 mm, a width of 100 mm, and a thickness of 0.20 mm was taken as a sample. The sample was ultrasonically cleaned in deionized water to remove impurities on the surface, and then dried in an oven at 105°C for 1 hour and cooled to room temperature in a desiccator. The dielectric constant (Dk) and dielectric loss tangent (Df) at a frequency of 10 GHz were measured using a cavity resonator device.
[0188] (4) Compatibility evaluation: Prepare a varnish-like resin composition according to Tables 3 to 5 (without adding inorganic fillers), place it in a 40 mL measuring barrel, and if the varnish-like resin composition is observed to be turbid, it is judged to be "incompatible"; if the varnish-like resin composition is observed to be clear, seal it and let it stand for 1 day, and observe the phase separation of the resin again after 1 day. If the resin phases are separated and one of the phases is rubbery, it is judged to be "incompatible", otherwise it is judged to be "compatible";
[0189] (5) Warpage at room temperature and after reflow: Take a laminate with a length of 240 mm, a width of 70 mm, and a thickness of 0.20 mm as a sample and measure it using a warpage tester. The unit is μm. The warpage at 30°C before reflow is recorded as "room temperature warpage", and the warpage at 30°C after reflow is recorded as "warpage after reflow".
[0190] ΔWarp = Warp after reflow soldering - Warp at room temperature;
[0191] The reflow parameters were set as follows: heating from 30°C to 260°C, and then cooling from 260°C to 30°C, at a rate of 3°C / min.
[0192] The test results are shown in Table 3, Table 4 and Table 5.
[0193] Table 3
[0194]
[0195]
[0196] Table 4
[0197]
[0198]
[0199] Table 5
[0200]
[0201]
[0202] Combined with the performance test data in Tables 3 and 4 above, it can be seen that the resin compositions provided in Examples 1-10 of the present invention have no compatibility problems such as resin agglomeration and precipitation. The metal foil-clad laminate prepared by impregnating glass fiber cloth with the resin composition in a varnish state has a dielectric constant Dk≤3.7 at 10GHz, a dielectric loss tangent Df≤0.004, a thermal expansion coefficient XY-CTE≤10ppm / ℃, and a glass transition temperature Tg of 220-260℃. It has a high glass transition temperature, a low thermal expansion coefficient, and excellent dielectric properties. In particular, the warpage at room temperature and the warpage after reflow soldering are low, and the Δ warpage after reflow soldering and at room temperature is ≤57μm, which has excellent deformation resistance and fully meets the performance requirements of high-speed packaging substrate materials.
[0203] According to the performance test data in Table 5, when there is no B component in the resin composition (Comparative Example 1), a thermoplastic polymer is added to obtain low dielectric loss, the resin composition in the varnish state is turbid, phase separation occurs after standing, the resin compatibility is poor, and the deformation resistance is poor due to insufficient crosslinking density, and the warping is large at room temperature and after reflow soldering; when the content of component A in the resin composition is too high (Comparative Example 2), the dielectric loss tangent angle of the laminate is too large, which does not meet the requirements of high-speed substrate materials for low dielectric loss; when the content of component B in the resin composition is too high (Comparative Example 3), the laminate is The thermal expansion coefficient increases and the glass transition temperature decreases, resulting in poor deformation resistance, which does not meet the low thermal deformation requirements of the substrate material; when the structure of component B in the resin composition does not contain the first structural unit and the second structural unit of the present invention (Comparative Example 4), the thermal expansion coefficient of the laminate increases and the glass transition temperature decreases, resulting in poor deformation resistance, which does not meet the low warping requirements of the substrate material; when there is no component A in the resin composition (Comparative Example 5), the glass transition temperature of the laminate decreases, the heat resistance decreases, the thermal expansion coefficient increases, the deformation resistance deteriorates, and the warping is large.
[0204] The applicant declares that the present invention uses the above embodiments to illustrate the resin composition of the present invention and the prepreg, laminate, and metal foil-clad laminate comprising the same, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises the following components in parts by mass: Component A 20-90 parts Component B 5-60 parts; The component A includes an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule; The component B is a benzocyclobutene resin, and the benzocyclobutene resin comprises at least one first structural unit and at least one second structural unit; The first structural unit has a structure as shown in at least one of Formula IA, Formula IB, and Formula IC: Wherein, R1 is vinylene or ethylene; The second structural unit has a structure as shown in Formula II: Wherein, R2 is vinyl, ethyl or phenyl.
2. The resin composition according to claim 1, characterized in that The molar percentage of the first structural unit in the benzocyclobutene resin is ≥5%, preferably ≥30%, and more preferably 30-60%; Preferably, the molar percentage of the second structural unit in the benzocyclobutene resin is 15-90%; Preferably, the benzocyclobutene resin further comprises a third structural unit, and the third structural unit has a structure as shown in Formula IIIA and / or Formula IIIB: Preferably, the molar percentage of the third structural unit in the benzocyclobutene resin is ≤40%, more preferably ≤30%, and even more preferably ≤20%.
3. The resin composition according to claim 1 or 2, characterized in that The number average molecular weight of the benzocyclobutene resin is 1,000-200,000.
4. The resin composition according to any one of claims 1 to 3, characterized in that The maleimide compound a1 contains two N-substituted maleimide groups in one molecule; Preferably, the maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenoxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenyl)cyclohexane oxy)phenyl)methane, 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4' - any one or a combination of at least two of bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether, bis(4-(4-maleimidophenoxy)phenyl)ether, and more preferably any one or a combination of at least two of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane, and 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane; Preferably, the amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl any one of or a combination of at least two of the following: 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, and 4,4'-diamino-3,3'-dihydroxybiphenyl; further The step is preferably a siloxane compound containing at least 2 primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, or a combination of at least two thereof; Preferably, the resin composition further comprises 1-50 parts by mass of component C, wherein component C comprises any one or a combination of at least two of epoxy resin, anhydride compound, active ester compound, and a compound having a carbon-carbon unsaturated double bond in the molecule, preferably a compound having a carbon-carbon unsaturated double bond in the molecule; Preferably, the compound having a carbon-carbon unsaturated double bond in the molecule includes any one or a combination of at least two of unsaturated polyphenylene ether, multifunctional vinyl compound, allyl compound, acrylate compound, acenaphthylene compound, and polybutadiene; Preferably, the resin composition further comprises 5-30 parts by mass of a thermoplastic polymer; Preferably, the thermoplastic polymer includes any one of styrene polymers, hydrogenated styrene polymers, and polyolefin resins, or a combination of at least two thereof; Preferably, the resin composition further comprises 0.01-5 parts by mass of a curing accelerator; Preferably, the curing accelerator includes any one of an acidic curing accelerator, an organic phosphorus curing accelerator, an imidazole curing accelerator, a pyridine curing accelerator, an amine curing accelerator, a peroxide, and an organic metal salt, or a combination of at least two thereof; Preferably, the resin composition further comprises 5-250 parts by mass of an inorganic filler; Preferably, the resin composition further comprises 0.01-10 parts by mass of a coupling agent; Preferably, the coupling agent comprises a silane coupling agent.
5. A resin film, characterized in that: The material of the resin film comprises the resin composition according to any one of claims 1 to 4; Preferably, the resin film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
6. A resin-coated copper foil, characterized in that: The resin-coated copper foil comprises a copper foil layer and a resin layer, and the material of the resin layer comprises the resin composition according to any one of claims 1 to 4.
7. A prepreg, characterized in that: The prepreg comprises a substrate and a resin composition according to any one of claims 1 to 4 attached to the substrate; Preferably, the resin composition is attached to the substrate by impregnation and drying.
8. A laminated board, characterized in that: The laminate comprises at least one prepreg according to claim 7.
9. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate includes at least one of the resin film according to claim 5 , the resin-coated copper foil according to claim 6 , and the prepreg according to claim 7 .
10. A printed circuit board, characterized in that: The printed circuit board comprises at least one of the resin film according to claim 5, the resin-coated copper foil according to claim 6, the prepreg according to claim 7, the laminate according to claim 8, and the metal foil-clad laminate according to claim 9.
Citation Information
Patent Citations
Thermosetting resin composition, prepreg comprising same, metal-foil-coated laminate and printed circuit board
CN109825081A
High-thermal-conductivity hydrocarbon resin-based prepreg and high-frequency copper-clad plate prepared from same
CN114437435A
Resin for high-frequency and high-speed copper-clad plate and polymerization method thereof
CN115677940A
Resin composition, prepreg and metal foil-clad laminated board
CN116410594A
Thermosetting resin composition, prepreg, laminate, printed wiring board and high-speed communication compatible module
JP2019011415A
Cited By
Resin composition and prepreg, metal clad laminate and high layer count substrate including the same
TWI919852B